Behavior, Awareness, and Sensitivity of Healthcare Providers in a Multicultural Environment - Abalos-Fabia, Russel Salvador; Khadrawi, Shadia Mohamed; Ellasus, Rosanta Oligan (Department of Nursing, Faculty of Medicine, Diponegoro University, 2018)
Background: The healthcare workforce of Saudi Arabia is characterized by diverse cultural backgrounds as a consequence of the employment of expatriate workers from various countries. The heterogeneity of both providers of health services and clients results in cultural barriers that affect the delivery care. It is paramount to evaluate the cultural competence of healthcare providers (HCPs) to maintain quality holistic care.Purpose: This study aimed to assess the cultural diversity experience, cultural competence behavior (CCB) and cultural awareness and sensitivity (CAS) of HCPs in a hospital setting of Saudi Arabia.Methods: This was a cross-sectional study involving a survey of 104 HCPs from medical, nursing and laboratory technology disciplines that were taken based on a total sampling procedure. Data collection was conducted using the Cultural Competence Assessment (CCA) tool that measured cultural diversity experience, CCB, and CAS. Data analysis was performed and presented in descriptive statistics, and significant findings were computed using independent samples t-test, analysis of variance (ANOVA), and Pearson correlation coefficient.Results: The characteristics of the respondents resulted in mean age of 38.7±10.4 who were predominantly Asians and nurses. The majority had working experience of 10 years and below, with more than half who had prior diversity training. Reported cultural diversity experience included all HCPs caring for Arab Middle Easterners and Asians and encountering at least one or more special population groups. There was an overall high cultural competence (5.28±0.46), high CCB (5.84±0.56) but only moderately high CAS (4.72±0.35). Significant differences were only identified between CCB scores and three demographic variables (racial/ethnic identification, the area of discipline and years of experience). No significant result was found between CAS scores and demographic variables as well as between CCB and CAS scores. Conclusion: Despite high CCB, the HCPs responded with lower CAS scores. Interventions should be initiated to increase CAS such as cultural diversity training and availability of cultural care resources.